2008
DOI: 10.1159/000191212
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Imbalance in Nonstimulated X-Adrenoleukodystrophy-Derived Lymphoblasts

Abstract: X-Adrenoleukodystrophy (X-ALD) is a peroxisomal disorder characterized by accumulation of very long chain (VLC) fatty acids, which induces alterations in cellular redox and induction of inflammatory disease, both of which are reported to play a role in pathogenesis of the severe form of the disease (childhood ALD). Here we report on the status of oxidative stress (NADPH oxidase activity) and inflammatory mediators in a X-ALD lymphoblast cell line under non-stimulated conditions. X-ALD lymphoblasts contain near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 78 publications
1
26
2
2
Order By: Relevance
“…The levels of C26:0 however, remained unchanged ( 31 ). Previous studies from our laboratory have shown that lovastatin, an inhibitor of HMG-CoA reductase and sodium phenyl acetate NAPA , can enhance VLCFA ␤ -oxidation and reduce VLCFA levels in human skin fi broblasts ( 32 ) and lymphoblasts ( 33 ) from X-ALD patients. Lovastatin also lowered the plasma levels of VLCFAs in X-ALD patients ( 34 ) and decreased the production of nitric oxide in X-ALD lymphoblasts ( 33 ).…”
Section: Cell Culturementioning
confidence: 82%
See 1 more Smart Citation
“…The levels of C26:0 however, remained unchanged ( 31 ). Previous studies from our laboratory have shown that lovastatin, an inhibitor of HMG-CoA reductase and sodium phenyl acetate NAPA , can enhance VLCFA ␤ -oxidation and reduce VLCFA levels in human skin fi broblasts ( 32 ) and lymphoblasts ( 33 ) from X-ALD patients. Lovastatin also lowered the plasma levels of VLCFAs in X-ALD patients ( 34 ) and decreased the production of nitric oxide in X-ALD lymphoblasts ( 33 ).…”
Section: Cell Culturementioning
confidence: 82%
“…Previous studies from our laboratory have shown that lovastatin, an inhibitor of HMG-CoA reductase and sodium phenyl acetate NAPA , can enhance VLCFA ␤ -oxidation and reduce VLCFA levels in human skin fi broblasts ( 32 ) and lymphoblasts ( 33 ) from X-ALD patients. Lovastatin also lowered the plasma levels of VLCFAs in X-ALD patients ( 34 ) and decreased the production of nitric oxide in X-ALD lymphoblasts ( 33 ). A number of other compounds, including 4-PBA ( 29 ), fenofibrate ( 25 ), and testosterone metabolites ( 35 ), have been shown to have the ability to lower VLCFA levels in X-ALD fibrobroblasts.…”
Section: Cell Culturementioning
confidence: 99%
“…Oxidative burden has been reported to play a role in the pathobiology of X-ALD ( 7,8,14,17,38 ). We previously reported reduced levels of GSH in the plaque area of the cALD brain ( 39 ).…”
Section: Redox Imbalance In White Matter Of Cald Brainmentioning
confidence: 94%
“…Furthermore, Vargas et al (2004) reported increased chemiluminescence and thiobarbituric acid reactive substances (TBARS) levels and decreased total antioxidant reactivity (TAR) in plasma from X-ALD patients. Oxidative damage has also been observed in fibroblasts (Fourcade et al 2008;Vargas et al 2004), plasma (Deon et al 2007;Rockenbach et al 2012), and lymphoblasts (Uto et al 2008) of X-ALD patients suggesting that the enhanced oxidative stress is systemic rather than localized. Moreover, Powers and co-workers reported oxidative modifications in post-mortem X-ALD brains with lipid peroxidation products predominantly present in the inflammatory demyelinative lesions and the adrenal cortex.…”
Section: Very Long-chain Fatty Acidsmentioning
confidence: 99%